The initial public offering of high-technology firms: female executive managers and innovation - Quintana-García, Cristina; Benavides-Velasco, Carlos Ángel (My University, 2013)
This study addresses how gender diversity in management teams influences the success of the IPO of research-intensive firms, and how critical indicators of innovation capabilities for those types of firms can mediate the gender effect.
Keywords: Mercado financiero; Empresas de tecnología; technology firms; financial market